Targeting type 2 inflammation in bullous pemphigoid: current and emerging therapeutic approaches - Toh, Wu Han; Lee, Hua-En; Chen, Chun-Bing (Frontiers in Medicine, 2023)
Bullous pemphigoid (BP) is one of the most common autoimmune bullous diseases, and mainly affects an elderly populaon with mulmorbidity. Exisng treatment opons for BP are mainly corcosteroids and immunosuppressants, which can have substanal side effects on these vulnerable paents that even exceed their therapeuc benefits. The blisters associated with BP result from IgG and IgE autoanbodies binding to the central components of hemidesmosome, BP180 and BP230, smulang a destrucve inflammatory process. The known characterisc features of BP, such as intense pruritus, urcarial prodrome, peripheral eosinophilia, elevated IgE, as well as recent expanding evidence from in vitro and in vivo studies implicate Type 2 inflammaon as an important driver of BP pathogenesis. Type 2 inflammaon is an inflammatory pathway involving a subset of CD4+ T cells that secrete IL-4, IL-5, and IL-13, IgE-secreng B cells, and granulocytes, such as eosinophils, mast cells and basophils. It is believed that effectors in Type 2 inflammaon may serve as novel and effecve treatment targets for BP. This review focuses on recent understandings of BP pathogenesis with a parcular emphasis on the role of Type 2 inflammaon. We summarize current clinical evidence of using Rituximab (B cell depleon), Omalizumab (an-IgE anbody), and Dupilumab (an-IL-4/13 anbody) in the treatment of BP. Latest advances in emerging targeted therapeuc approaches for BP treatment are also discussed.